Development of a Cognitive Assessment Instrument for Simple Business, Energy and Aircraft Materials via Wordwall - Angelika, Neindea; Supriyadi, Supriyadi; Djunaidi, Djunaidi (Jurnal Penelitian Pembelajaran Fisika, 2024)
Cognitive assessment of kids who still frequently use paper documents and certain school-provided software. The objective of this study is to develop a legitimate, dependable, efficient, and useful tool that may be used to teach static electricity concepts through wordwalls. This study use the ADDIE model in conjunction with the Research and Development technique. Purposive sampling is the sampling technique used, taking into account samples that have finished business, energy, and basic aviation material for science education. 52 individuals served as the samples. The study is being conducted at SMP 1 PGRI in Semarang City. Using SPSS software version 2019 and Ministep, the data analysis technique involves testing the validity, reliability, efficacy, and practicality of test instruments and questionnaires. The study's findings demonstrate that the creation of a wordwall-based cognitive instrument on static electricity learning outcomes is valid, dependable, and practically implemented, as evidenced by the instrument's 0.79 sufficient category score, 74.9 average score, and 61.40% production rate based on student responses. This means that future researchers can build on this tool to suit their needs and the reference tools that are used to assess learning.